Construction of a lncRNA–mRNA Co-Expression Network for Nasopharyngeal Carcinoma - Fan, Chunmei; Xiong, Fang; Tang, Yanyan; Li, Panchun; Zhu, Kunjie; Mo, Yongzhen; Wang, Yumin; Zhang, Shanshan; Gong, Zhaojiang; Liao, Qianjin; Li, Guiyuan; Zeng, Zhaoyang; et al. (Frontiers in Oncology, 2022)
Long non-coding RNAs (lncRNAs) widely regulate gene expression and, thus, play important roles in the pathogenesis of human diseases, including malignant tumors. However, the functions of most lncRNAs remain to be elucidated. In order to study and screen for novel lncRNAs with important functions in the carcinogenesis of nasopharyngeal carcinoma (NPC), we constructed lncRNA expression profile of 10 NPC tissues and 6 control through a gene microarray. We identified 1,276 lncRNAs, of which most are unknown, with differential expression in the healthy and NPC tissues. In order to provide clues to the functions of these unknown lncRNAs, we first constructed a co-expression network of lncRNAs and mRNAs using bioinformatics and systems biology methods. Moreover, mRNAs were clustered and enriched by their biological functions, and those lncRNAs have similar expression trends with mRNAs were defined as functional moleculars with potential biological significance. The moleculars may help identify key lncRNAs in the carcinogenesis of NPC and provide clues for in-depth study of their functions and associated signaling pathways. We suggest the newly identified lncRNAs may have clinic value as biomarkers and therapeutic targets for NPC diagnosis and treatment.